Sudden Sensorineural Hearing Loss in the Only Hearing Ear: Large Vestibular Aqueduct Syndrome - Kemal Koray Bal; Onur Ismi; Helen Bucioglu; Yusuf Vayısoğlu; Kemal Gorur (Case Reports in Otolaryngology)
Sudden hearing loss in the only hearing ear cases are rarely published in the English literature; most of the cases are idiopathic. It is an otologic emergency needing urgent treatment. Delayed diagnosis can interfere with patient’s social life with interrupting the verbal communication. In this case report we presented a 33-year-old female patient having sudden sensorineural hearing loss in the only hearing ear diagnosed as bilateral large vestibular aqueduct syndrome.